Investigation of the effect of anodization time and annealing temperature on the physical properties of ZrO2 thin film on a Si substrate - Goh K.H.; Lee H.J.; Lau S.K.; Teh P.C.; Ramesh S.; Tan C.Y.; Wong Y.H. (Institute of Physics Publishing, 2023)
Annealing; Grain size and shape; Morphology; Scanning electron microscopy; Silica; Silicon; Sodium hydroxide; Sputtering; Zircon; Zirconia; Annealed samples; Annealing temperatures; Anodization process; Anodization time; Anodizations; Fourier transform infrared microscopies; Scherrer equations; ZrO2; Thin films